Development of a capillary plasma pump with vapour bubble for water purification: experimental and theoretical investigation. (12th September 2016) - Uehara, S; Ishihata, K; Nishiyama, H
Abstract: This paper describes the development of a small-sized reactive plasma pump driven by capillary bubble discharge for the purification of treated water. The apparatus we developed decomposes the pollutants in the water by using chemical species generated by the plasma discharge. The resulting stream of bubbles obviates the need for an external gas supply or pump to transport the water. A high-speed camera was used to investigate the bubble dynamics responsible for the pumping effect, which is achieved by selecting the shape of the capillary such that the bubble ejections within enhance the 'self-repetition' action required for the pumping motion. Our experiments showed that optimal bubble generation requires a consumed power of 17.8 W. A theoretical model was developed to investigate the pumping mechanism. We solve the problems associated with liquid oscillations in the U-shaped water reservoir by employing a non-uniform cross-sectional area in our model. The chemical reactivity of the device was confirmed by using emission spectroscopy of OH radical and by measuring the decomposition of methylene blue.